Fungos presentes em sedimentos marinhos e lacustres da Antártica: taxonomia, diversidade e bioprospecção de metabólitos bioativos - Mayara Baptistucci Ogaki (2019)
Some ecosystems, such as deep sea, hypersaline lagoons, volcanic substrates, deserts and polar regions, have physicochemical conditions considered unfavorable to life and are characterized by the presence of microbial communities known as extremophiles, which may be composed mainly of viruses, bacteria, archaea and fungi. In extreme ecosystems, fungi have ecological importance in nutrient cycling, and due to their high genetic and metabolic plasticity, which throughout its evolution have been conditioned by large variations in salinity, temperature, radiation, water availability, pressure, acidity, etc. In Antarctica, the selective pressure provided by weather conditions, especially low temperatures and poor water availability, may have selected fungi with different survival strategies, including antifreeze production, changes in cell membrane composition and production of differentiated primary and secondary metabolites. Considering the diversity and potential production of biomolecules presented by extremophile fungi, basic and applied studies involving these microorganisms are of great interest because they represent a portion of the world's biodiversity and also a rich source of substances with potential application in biotechnological processes. Thus, the present study aimed to characterize the fungal communities present in Antarctic marine and lake sediments in order to evaluate them as potential producers of bioactive substances. In the different substrates evaluated were obtained 486 fungal isolates belonging to 111 operational taxonomic units (OTUs). In the Southern Shetlands marine sediment samples, most taxa belonged to the Penicillium genus, with abundance of P. allii-sativi, P. palitans, P. solitum and P. chrysogenum, as well as Pseudoagymnoascus verrucosus and Acremonium fusidioides species. Regarding the prospecting of bioactive metabolites produced by these marine fungi, the extracts of 12 taxa were able to inhibit the growth of the phytopathogenic fungus Cladosporium sphaerospermum, among which the extracts of P. solitum and P. chrysogenum were the most active. All extracts have nematicidal activity. The extracts of 30 isolates (96.8%) presented herbicidal activity, of which 58% showed maximum inhibition of Allium schoenoprasum and/or Lactuca sativa germination, among which P. allii-sativi, P. chrysogenum, P. solitum, P. palitans and A. fusidioides. were the most active. Different isolates of Penicillium spp. Potential producers of substances with antiplasmodial and trypanosomicidal activity were also shown. The eight extracts of the most active marine fungi were chemically characterized by their H1 Nuclear Magnetic Resonance (H1 NMR) spectra, indicating the presence of aromatic molecules, which may be responsible for the expressive biological activities. The fungal communities present in lake sediments were analyzed from lakes impacted by anthropic activity and non-impacted lakes, both sampled in the archipelago of the South Shetlands. In the sediment samples from lakes impacted by anthropic activity, 63 OTUs were characterized and taxa Pseudeurotium hygrophilum, Pseudogymnoascusus verrucosus and Neobulgaria sp. occurred more frequently. In the Central Lake sediment, near the Antarctic stations, higher metal concentrations and lower diversity and fungal richness values were detected, unlike the North Lake, far from the stations. The extracts of 40 isolates (15.4%) showed at least one biological activity against T. cruzi, C. sphaerospermum or herbicide, with emphasis on extracts of different P. hygrophilum isolates, which showed selective activity for the mentioned targets. From sediment samples from non-impacted lakes, 42 OTUs were identified, among which the endemic and/or psychophilic taxa Thelebolus globosus, Vishniacozyma victoriae, Antarctomyces psychrotrophicus and P. verrucosus were the most frequent. Among the extracts produced by these fungi, 60 (30.8%) showed at least one biological activity against Leishmania amazonensis, Plamodium falciparum, T. cruzi, C. sphaerospermum or herbicide; However, the activities presented were not species dependent. Despite the different unfavorable conditions for life in Antarctic marine and lake sediments, the fungal communities were rich and diverse, with high dominance of cosmopolitan species. The data obtained contribute to a better knowledge of the fungal communities present in marine and lake sediments, considered oligotrophic, since many species were reported for the first time. For lakes near the Antarctic stations and affected by tourism in the region, increased anthropogenic activities may affect the diversity and composition of the present mycota, and this may represent a useful model for the study of anthropic impact in Antarctica. Finally, fungi obtained from sediments represent a rich source of bioactive metabolites, which can be exploited as prototypes for new drugs and herbicides less toxic to agriculture.